Tradisi Maulid Nabi di Kalangan Masyarakat Pesantren - Hamim, Thoha (Religió: Jurnal Studi Agama-agama, 2014)
The Maulid Mawlid Festival of the Prophet Muhammad is one of the Islamic popular events mostly held in pesantren. It launches almost in every territory of Islamic world, after popularized by abu Abû said Sa‘îd al-kakburi Kakburî (1250-1260). Historically, it was a heritage initially acknowledged by the Dinasty of Fât}}imîyah (909-1171 M). At the beginning, the Dinasty dynasty used the Maulid Mawlîd Festival to gain a fancy of Moslems to support their authority of Islamic leadership. It used to strengthen their political ways to gain many public opinions in relation with their genealogical relationship with the prophet. The affirmation of genealogical relationship was needed as a tool of propaganda politically so that their right to inherit prophet authority has strong legitimation. In addition, the mauled festival does not only function to liven up Moslem community affection toward the prophet but also symbolically function as a psychological antidote to muffle the pain after having war. At the end, Moslem intellectuals started to scrutinize the festival and discuss its essence. However, such festival creates a big debate around Moslem scholars who have pro and contra in seeing it for instance al-Suyût}}î who sees the festival in contradictive way. This paper aims to explore the debates and discourses concerning the Maulid Mawlîd Festival. The discussion over Islamic religious tradition constitutes a strategy to test the level of good argument proposed by each groups of Islamic organization.